2009
DOI: 10.1016/j.jvs.2008.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Intra-operative DynaCT improves technical success of endovascular repair of abdominal aortic aneurysms

Abstract: Most graft-related complications that mandate early reintervention following EVAR are due to remediable technical problems which are not identified by uniplanar completion angiography alone. DynaCT is a feasible intra-operative adjunct to completion angiography, which improves intra-operative quality control during endovascular repair of abdominal aortic aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 25 publications
1
33
3
Order By: Relevance
“…7 The results of the study by Biasi et al showed that early complications were due to technical failures in up to 86% of cases and supposedly corrected with better intra-operative imaging. 7 The use of CBCT resulted in adjunctive procedures in 6.25% of the patients in the study by Biasi et al,7 while in the present study 8.1% of the patients had benefited from the CBCT intra-operatively. Abbruzzese et al reported adjunctive procedures in 25% of patients of whom approximately 14% were technical failures and the other procedures were to treat endoleaks.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…7 The results of the study by Biasi et al showed that early complications were due to technical failures in up to 86% of cases and supposedly corrected with better intra-operative imaging. 7 The use of CBCT resulted in adjunctive procedures in 6.25% of the patients in the study by Biasi et al,7 while in the present study 8.1% of the patients had benefited from the CBCT intra-operatively. Abbruzzese et al reported adjunctive procedures in 25% of patients of whom approximately 14% were technical failures and the other procedures were to treat endoleaks.…”
Section: Discussionmentioning
confidence: 98%
“…This issue has been described earlier and has been a major limitation of the technique. 7,8 A software upgrade during the trial enabled a vertical (portrait) mode, which is superior in studying the stent graft. The detector is simply rotated 90 degrees thus allowing capture of a greater cranio-caudal segment (30 Â 40 cm).…”
Section: Methodsmentioning
confidence: 99%
“…CT-like imaging with the angiographic C-arm enables the surgeon to diagnose this complication intraoperatively and correct it. A group from University of London (Biasi et al, 2009) demonstrated in a study of 80 patients undergoing EVAR that 3D imaging with DynaCT in the operating room was able to detect endoleaks in 5 patients. These endoleaks were not detected by conventional completion angiography.…”
Section: Thoracic Endovascular Aortic Repair (Tevar)mentioning
confidence: 99%
“…Intraoperative real-time three-dimensional transoesophageal echocardiography and dynamic computed tomography (Dyna-CT) [7,8] are other examples of ongoing development. Modern angiography systems offer advanced imaging, postprocessing image fusion capabilities with previously acquired three-dimensional volumes (e.g., CT, MRI, PET, single photon emission computed tomography images), and real-time threedimensional intraoperative navigation.…”
Section: Imagingmentioning
confidence: 99%